Design and Validation of a Self-care Evaluation Instrument to Prevent Diabetic Foot - Herrera Guerra, Eugenia del Pilar; Bautista Arellanos, Lili Rosa (Investigación y Educación en Enfermería, 2022)
Objective. This work sought to design and validate a self-care instrument to prevent diabetic foot in Colombian adults with diabetes. Methods. Psychometric study in which an instrument was designed to measure self-care to prevent diabetic foot according to the Medium Range Theory of Self-care in chronic diseases. With a sample of 230 people with type-2 diabetes, construct validity was determined through exploratory and confirmatory factor analysis. Internal consistency was calculated with Cronbach’s alpha coefficient. Results. Favorable evidence of construct validity was obtained with a model consisting of three scales: self-care maintenance with a three-factor structure (accumulated variance 43%), α = 0.7, with good fit (????2= 64.698, p = 0.001; RMSEA = 0.066; RMSSR = 0.071; CFI = 0.936, NNFI = 0.910). Monitoring of self-care with presence of symptoms a two-factor structure was found, α = 0.950, with good fit (????2 = 266.837, p = 0.000; RMSEA = 0.321; RMSSR = 0.057; CFI = 0.848; NNFI = 0.789); and without symptoms, a single-factor structure (cumulative variance 84%), α = 0.9, acceptable fit (????2= 377.327, p < 0.001; RMSEA = 0.355; RMSSR = 0.073; CFI = 0.832; NNFI = 0.764). And self-care management with two-factor structure (cumulative variance 53.7%) α = 0.7, with good fit (????2 = 14.317, p = 0.014; RMSEA = 0.144; RMSSR = 0.063; CFI = 0.905; NNFI = 0.809). Conclusions. The resulting instrument has adequate psychometric properties, consistent with the theoretical model of self-care in chronic diseases. Its use is recommended to evaluate self-care to prevent diabetic foot in populations similar to the study population.